Unnoticed impacted foreign body ear presenting as chronic suppurative otitis media with postaural fistula: a rare case - Prasad, K. C.; S., Sreelekshmi; K., Abhilasha; P. K., Anjali; G., Induvarsha; N., Harshitha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Foreign body ear, especially in the external auditory canal are common in adults and children. Most common age group presenting with foreign body is 2 to 10 years. Most common foreign bodies are seeds insects, paper, chalk pieces etc. Most common complications of foreign body ear are pain, bleeding, foul smelling discharge, otitis externa and irritation of ear. There are chances of external auditory canal laceration, bleeding, infection, perforation of tympanic membrane, dislodgement of foreign body towards inner region during the time of removal. This is a case of unnoticed impacted foreign body presented as chronic suppurative otitis media with postaural fistula, found on table broomstick foreign body which was removed using canaloplasty and further managed with tympanoplasty and cortical mastoidectomy.